Aproveitamento da casca de arroz para a produção de xilitol e sílica xerogel - Rambo, Magale Karine Diel (2009)
The generation of residual materials and its unavoidable disposal in the environment has been a reason of great concern, not only environmentally but also economically. The use of these renewable residual feedstocks, not only for the production of heat and energy, but also for the generation of technological products, has become a priority. In this study, it was investigated the physico-chemical and fermentative processes for the good use of the agro-industrial residue rice husks. The husks, resulting from the rice processing, has been also used, even incipiently, for the generation of heat to dry grains and electrical energy. As a result of this process, rice husk ash (RHA) is available, very rich in silica (sílica), representing a potential future source of industrial raw material. Micronized RHA, obtained from micro grinding process, was used to produce three types of silica xerogels, which were tested as additives for rice cultivation. The good results demonstrated the feasibility of the use of the xerogel silicas in substitution of agrochemical products. The influence of the process parameters (pH, time, concentration) was determined by means of the response surface methodology (RSM). The maximum production yields of sodium, potassium and calcium silica xerogels were 98%, 95% and 75%, respectively. The silica produced was characterized and analyzed by the following techniques: X-ray fluorescence and X-ray diffractometry (XRF, XRD), Fourier-transform infrared spectrometry (FTIR), scanning electronic microscopy (SEM), particle size distribution determined by laser diffraction, specific surface area by BET method (Brunauer, Emmett e Teller), and determination of metals by inductively coupled plasma emission optical pectrometry (ICP-OES). The production of xylose was studied by acid hydrolysis of rice husk, under pressure, in autoclave. Then, the xylose was converted into xylitol by fermentation. The process parameters, temperature and reaction time, were adjusted by RSM. Fermentations were performed using the yeast species Candida guilliermondii and Candida tropicalis, with maximum yields of 40% and 8%, respectively. The influence of various types of pretreatment of the sample was evaluated, demonstrating the potential yields of 66% and 64%, respectively, when the husk was treated with hydrogen peroxide and ammonium hydroxide solutions. When using physical pretreatment (ultrasound), yields up to 62% can be obtained. The influence of the variation of acid concentration and pH of the hydrolyzate on the yields was also evaluated. The contact time and amount of activated carbon added to the hydrolyzate exerts great influence on the process yield. The products obtained - xylose and xylitol - were identified and quantified by liquid chromatography coupled to mass spectrometer (LC-MS/MS) with electrospray ionization in positive mode. Results of the second order RSM applied to obtain silica xerogel as well as xylitol were evaluated by analysis of variance (ANOVA). The efficiency of the processes studied here shows that they may be interesting alternatives of use of biomass residue rice husk, with considerable economic potential and positive environmental impact.